2011
DOI: 10.1111/j.1600-0838.2009.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of platelet‐rich plasma on the neovascularization of surgically created equine superficial digital flexor tendon lesions

Abstract: The repair process of tendon injuries, which are common in both human and equine athletes, is slow and the quality of the repair tissue is often inferior to the original tendon tissue, which frequently leads to re-injury. The relatively poor vascularization of tendons is considered to be one of the reasons for their limited healing potential. Recently, platelet-rich plasma (PRP), an autologous concentrate of platelets, rich in growth factors, has been shown to enhance the repair process of injured tendons. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
101
1
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(121 citation statements)
references
References 40 publications
4
101
1
9
Order By: Relevance
“…These results could be attributed to the powerful and long-term analgesic and anti-inflammatory effect of intra tendentious PRP via its growth factors. Also, different authors attributed these findings to paramount regenerative role of intratendinous PRP which enhance early granulation formation, cellular proliferation and differentiation and gradual arrangement of tendon fibers bundle [6,29]. These findings were supported histopathologically in the present study and in another reported one [30].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results could be attributed to the powerful and long-term analgesic and anti-inflammatory effect of intra tendentious PRP via its growth factors. Also, different authors attributed these findings to paramount regenerative role of intratendinous PRP which enhance early granulation formation, cellular proliferation and differentiation and gradual arrangement of tendon fibers bundle [6,29]. These findings were supported histopathologically in the present study and in another reported one [30].…”
Section: Discussionsupporting
confidence: 81%
“…The exact mechanisms of PRP on the inflammatory response after acute tendon injury is not excluded yet, but many studies postulated that the therapeutic effects of PRP in tendon repair could be attributed to the high content of PRP in many growth factors and anti-inflammatory cytokines such as PDGF, IGF-I, bFGF, VEGF and HGF, EGF, DAF, platelet factor 4, ECGF, FGF and stromal cell derived factor 1α [6,[11][12][13]. These factors had major effects on tendon repair via promoting angiogenesis, fibroblast proliferation, leukocyte chemotaxis, collagen deposition, and remodeling [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…In the follow-up period all patients ran a combined total of 64 races and horses with severe injury started in 58% races, moderately-injured horses ran in 30% races and mildly injured animals ran in 12%, respectively. Bosch et al (2011) recommended only one intralesional application of PRP in the acute stage of the injury but Textor (2011) who also reported management of SDFT injuries in the acute stage recommended repeated application. In our study we applied PRP in all cases only once because the lesion was ultrasonographically not visible during the control examination.…”
Section: Discussionmentioning
confidence: 99%
“…al., 2012). Bosch et al (2010Bosch et al ( , 2011 studied the healing of a mechanically-induced experimental central core lesion in the SDFT of a horse and found, after only one application of PRP into the lesion, a significant positive effect on the biochemical, biomechanical and histological characteristics of the healing process. The healed tissue was rich in collagen fibres and glycosaminoglycans compared to the control group.…”
mentioning
confidence: 99%
“…To this end, platelet rich plasma (PRP), a natural concentrate of many growth factors [182][183][184], is under intense investigation. PRP has been proposed as a therapy for the treatment of equine tendon injuries, with data demonstrating development and maturation of a healing tendon tissue, based on improved metabolic activity, increased failure strength and elastic modulus of the repairing tissues and increased neovascularisation, over the saline injected counterparts in an equine superficial digital flexor tendon model [185][186][187][188]. In a clinical setting, PRP injections have been used under various identifying names for decades [189,190]; however long-term, large and blinded studies have yet to be reported, with current data contradicting each other.…”
Section: Delivery Of Biological Molecules -Growth Factorsmentioning
confidence: 99%